Frying process in Food Service in Londrina - Dijuli, Deise Aparecida da Silva; Seibel, Neusa Fátima (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 41 No especial (2025): Conectur 2025, 2025)
Frying aims to change the sensory properties of food, providing crispness, color, flavor and aroma characteristics. Frying time depends on the type and thickness of the food, the temperature of the oil and the method applied. The objective of the work was to monitor and evaluate the frying process on site and analyze the oil used with quick test. In three food service kitchens in Londrina, the frying process was monitored and evaluated using pre-determined parameters and the oil used was analyzed by the 3M™ Oil and Fat Monitor. Two units presented a similar process and the third was different, due to the production volume, but in all of them a lack of control over the portion of food and frying time was identified, in addition to other inadequate practices. Thus, the need to raise awareness and instruct supervisors and food handlers who carry out the frying process was highlighted, concluding that the implementation of spreadsheets, training and standardization of the process will assist in the quality of products without financial losses.